Improving the dissolution rate of the anticancer drug dabrafenib - Rai, Sunil K.; Gunnam, Anilkumar; Mannava, M. K. Chaitanya; Nangia, Ashwini K. (Crystal Growth & Design, 2020)
Dabrafenib (DBF) is an anticancer drug with selective B-Raf (BRAF) inhibition activity. In 2013, DBF was approved by the U.S. Food and Drug Administration (US-FDA) as a dabrafenib mesylate salt (DBF center dot MS). Because of insolubility in aqueous medium, specifically at the pH 4-8 biorelevant range, DBF is a Biopharmaceutics Classification System (BCS) Class II drug (i.e., low solubility and high permeability). Therefore, screening of novel salts and cocrystals was carried out using Generally Recognized as Safe (GRAS) coformers. A total of 10 salts/cocrystals including the mesylate salt were found to be stable under the crystallization conditions. Among acidic coformers, methane sulfonic acid (MS) and saccharin (SACH) formed salts, while fumaric acid (FA), succinic acid (SA), and adipic acid (ADA) gave cocrystals. However, monoamines formed a monohydrate salt where the water molecule is hydrogen bonded with the aminopyrimidine moiety of DBF. The replacement of monoamines with ethylenediamine (EN) dislocated the water molecule near the free amine of EN in the crystal structure with a change in space group from triclinic (P (1) over bar) to monoclinic (P2(1)/n). Dissolution measurements at pH 1.2 (0.1 N HCl) showed that DBF center dot EN superset of H2O dissolved rapidly compared to the DBF.MS salt (the dissolution rate of DBF center dot EN superset of H2O and DBF center dot MS is 11 and 2 times faster than that of DBF). Structure-activity relationship analysis showed that bonding of the aminopyrimidine moiety with strong hydrogen bond synthons inhibited dissolution, whereas a loosely bound or free site at the aminopyrimidine moiety enhanced the dissolution rate. Finally, a cytotoxicity study was performed for DBF, DBF center dot MS, and DBF center dot EN superset of H2O, which showed that DBF center dot EN superset of H2O is safe for normal cells and yet equally potent against cancer cells. Crystal engineering of an improved formulation of dabrafenib center dot ethylenediamine hydrate is presented as a new anticancer drug.